2014
DOI: 10.4161/org.27879
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells support hepatocyte function in engineered liver grafts

Abstract: Recent studies suggest that organ decellularization is a promising approach to facilitate the clinical application of regenerative therapy by providing a platform for organ engineering. This unique strategy uses native matrices to act as a reservoir for the functional cells which may show therapeutic potential when implanted into the body. Appropriate cell sources for artificial livers have been debated for some time. The desired cell type in artificial livers is primary hepatocytes, but in addition, other sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…20 However, the ability to reproducibly generate a robust recellularized construct has proven elusive. 7,11,17,21 Early studies attempted to seed the scaffold with primary hepatocytes, and these efforts were followed by the use of stem and progenitor cells. 10,11,17,21,22 More recent work has demonstrated the importance of cell-to-cell interactions, thus highlighting the importance of multiple cell lineages in recreating a functional native liver.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…20 However, the ability to reproducibly generate a robust recellularized construct has proven elusive. 7,11,17,21 Early studies attempted to seed the scaffold with primary hepatocytes, and these efforts were followed by the use of stem and progenitor cells. 10,11,17,21,22 More recent work has demonstrated the importance of cell-to-cell interactions, thus highlighting the importance of multiple cell lineages in recreating a functional native liver.…”
mentioning
confidence: 99%
“…7,11,17,21 Early studies attempted to seed the scaffold with primary hepatocytes, and these efforts were followed by the use of stem and progenitor cells. 10,11,17,21,22 More recent work has demonstrated the importance of cell-to-cell interactions, thus highlighting the importance of multiple cell lineages in recreating a functional native liver. 21 Transplantation of the recellularized construct has resulted in rapid graft thrombosis, likely secondary to exposed collagen in the deendothelialized vasculature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of multiple cell types, like hepatocytes and MSCs, with acellular matrixes for organ reconstruction is another field with promising results (Kadota et al, 2014).…”
Section: Biomimetic Scaffolds and Stem Cellsmentioning
confidence: 99%
“…Multipotent mesenchymal stromal cells, also called mesenchymal stem cells (MSC), support the growth of rodent hepatocytes by favoring cellular adhesion in vitro [12,13] and in vivo [14]. Several studies in rodents have shown that cotransplantation of free primary hepatocytes with rat MSC prolonged graft function with a decrease in alanine transaminase (ALT), aspartate transaminase (AST), and bilirubin [15][16][17].…”
Section: Introductionmentioning
confidence: 99%